The Influence of Income and Number of Family Members on the Welfare of Farming Families in Gerokgak Village, Gerokgak District - Putu Sulasni; I Wayan Suwendra (Jurnal Akuntansi Profesi, 2021)
In a family, income and the number of family members is an important element that must be considered because it can affect the welfare of a family. The desire to form a prosperous family can be achieved if the needs of family members can be fulfilled. The needs of the family members will be easier to achieve if family members can earn a high income. The purpose of this study was to determine whether there is an influence of income and number of family members on the welfare of farming families in Gerokgak Village, Gerokgak District. The type of research was causal research with a quantitative approach. The population in this study amounted to 644 households who lived in Gerokgak Village and worked as farmers with a sample of 247 respondents who were determined using the Slovin formula. The data collection method used was a questionnaire which is analyzed using statistical techniques t test and f test. Based on this research, that there is an influence between income and the number of family members on the welfare of farmer families in the Gerokgak Village both individually and collectively.